Implementasi Algoritma Multi-Factor Evaluation Process Pada Website Sistem Pendukung Keputusan Minat Siswa - Pratama, Fajar; Widodo, Agung Mulyo (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
After graduating from high school, students often have difficulty in determining the right major.The challenges faced include the lack of clear guidelines and criteria in choosing a major, as wellas the selection process which is still traditional and subjective. To overcome these obstacles, thisarticle suggests the implementation of a website-based Decision Support System (DSS) using theMulti-Factor Evaluation Process (MFEP) algorithm. This DSS was developed to help studentschoose a major that suits their interests and potential. The methods used in this study includeliterature studies, observations, interviews, and questionnaires. The results of the study indicatethat the use of a web-based DSS with the MFEP algorithm is able to provide more effective andobjective recommendations in helping students choose a major.